1968
DOI: 10.2323/jgam.14.19
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Erwinia Herbicola

Abstract: Taxonomic studies were carried out on yellow-pigmented bacteria which were found widely in paddy rice, fruit and other related plant materials, and they were included in Erwinia herbicola on the basis of flagellation and biochemical characteristics.Determination, nomenclature and relation to other allied bacteria of this species were discussed.Taxonomic position of the strains of Pseudomonas perlurida and Ps. tri folii, which were previously reported by the authors, was corrected.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
1

Year Published

1970
1970
1989
1989

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 11 publications
1
5
1
Order By: Relevance
“…bb[Pseudomonas] trifolii" LMG 2598 groups with a Tm(e) of 77°C versus Escherichia coli in the rRNA branch of the Enterobacteriaceae (Table 10). Thus, our results do not contradict the proposed and generally accepted inclusion of " [Pseudomonas] trifolii" in Erwinia herbicolu (33). Recently, Verdonck et al (56) showed that this strain belongs phenotypically in Erwinia herbicola phenon 9.…”
Section: Resultscontrasting
confidence: 43%
“…bb[Pseudomonas] trifolii" LMG 2598 groups with a Tm(e) of 77°C versus Escherichia coli in the rRNA branch of the Enterobacteriaceae (Table 10). Thus, our results do not contradict the proposed and generally accepted inclusion of " [Pseudomonas] trifolii" in Erwinia herbicolu (33). Recently, Verdonck et al (56) showed that this strain belongs phenotypically in Erwinia herbicola phenon 9.…”
Section: Resultscontrasting
confidence: 43%
“…The characteristics of the strains examined in the present study compare favorably with the descriptions of previous human isolates (Table 3) as well as nonphytopathogenic erwinias isolated from various plant (3,11,12) and nonplant hosts (17,23). The proper identification of Erwinia in the diagnostic laboratory would appear to depend on the scrutiny of all yellow chromogenic, fermentative bacilli which generally are anaerogenic.…”
Section: Downloaded Fromsupporting
confidence: 78%
“…Previous studies comparing the nucleoside phosphotransferase activity of many gramnegative bacteria have shown that S. marcescens (4, 6, 9-11, 14), many Flavobacterium strains (7, 15), Erwinia herbicola and some E. carotovora strains (10,11), and most strains of Enterobacter liquefaciens (4) were distinctive in their ability to synthesize only 5'-nucleotide rather than 3'(&2')-nucleotide. Aeromonas (14), Escherichia coli (6, 7, 9, 10), Citrobacter (9), Enterobacter (6, 9-11), Proteus (6, 9, 14), and Salmonella (9, 14) synthesized primarily 3'(&2')-nucleotide and small amounts of 5'-nucleotide.…”
Section: Discussionmentioning
confidence: 99%